2002
DOI: 10.1046/j.1365-8711.2002.05406.x
|View full text |Cite
|
Sign up to set email alerts
|

Photometry of four binary subdwarf B stars and the nature of their unseen companion stars

Abstract: We present light curves of four binary subdwarf B stars (sdB), Ton 245, Feige 11, PG 1432+159 and PG 1017−086. We also present new spectroscopic data for PG 1017−086 from which we derive its orbital period, P=0.073 d, and the mass function, fm=0.0010±0.0002 M⊙. This is the shortest period for an sdB binary measured to date. The values of P and fm for the other sdB binaries have been published elsewhere. We are able to exclude the possibility that the unseen companion stars to Ton 245, Feige 11 and PG 1432+15… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
1

Relationship

5
4

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 27 publications
4
64
1
Order By: Relevance
“…Maxted et al (2002) reported the detection of a significant reflection effect, but no eclipses in the light curve. Taking these informations into account, one can constrain the inclination angle to be lower than 73…”
Section: Late Main Sequence Stars and A Potential Brown Dwarfmentioning
confidence: 98%
See 1 more Smart Citation
“…Maxted et al (2002) reported the detection of a significant reflection effect, but no eclipses in the light curve. Taking these informations into account, one can constrain the inclination angle to be lower than 73…”
Section: Late Main Sequence Stars and A Potential Brown Dwarfmentioning
confidence: 98%
“…No signatures of a main-sequence companion within the given mass range are visible in the flux distribution or in the spectrum f . These informations are taken from (1) Bloemen et al (2010), (2) Charpinet et al (2008), (3) Drechsel et al (2001), (4) Edelmann (2008), (5) Farihi et al (2005), (6) Geier et al (2007), (7) Geier et al (2010a), (8) Geier et al (2008a), (9) Koen (2007), (10) Koen (2009), (11) Lisker et al (2005), (12) Maxted et al (2002), (13) Maxted et al (2004), (14) Østensen (priv. comm.…”
Section: White Dwarfsmentioning
confidence: 99%
“…Due to the early spectral type of the primary star, the gravity darkening (Van Grootel et al 2013a;Drechsel et al 2001;Geier et al 2011d;Maxted et al 2002;Klepp & Rauch 2011;Østensen et al 2008Wood & Saffer 1999;Almeida et al 2012;Barlow et al 2013). The open dots represent other sdB binaries from the literature.…”
Section: Photometric Analysismentioning
confidence: 99%
“…The binary scenario is supported by the finding of numerous low-mass WDs in binary systems in the field, with * Based on observations made with the NASA/ESA Hubble Space Telescope, obtained by the Space Telescope Science Institute. STScI is operated by the Association of Universities for Research in Astronomy, Inc., under NASA contract NAS 5-26555. the companion being another WD, a neutron star, or a subdwarf B star (Marsh et al 1995;Maxted et al 2002). However, single He-core WDs have also been observed (Marsh et al 1995;Kilic et al 2007), raising the possibility that severe mass loss on the first ascent of the giant branch can prevent ignition of helium burning.…”
Section: Introductionmentioning
confidence: 99%